Implementasi Proyek Penguatan Profil Pelajar Pancasila untuk Menumbuhkan Karakter Siswa di SDN Jombatan 6 Jombang - Fatmawati, Irma Dyah; Rahma Pratiwi, Emy Yunita; Widjaja, Wanty (Prodi Pendidikan Guru Sekolah Dasar, 2024)
The persisting issue of lacking empathy and environmental awareness among students at SDN Jombatan 6 Jombang—evident in neglected surroundings and substantial waste accumulation—remains a recurring concern. This study aims to implement the Pancasila Student Profile Strengthening Project (English: Projek Penguatan Profil Pelajar Pancasila [P5]) activities to cultivate students’ character and outline execution strategies. Employing a qualitative descriptive approach, this research examined subjects in light of existing phenomena. Participants include the school principal, fourth-grade teachers, all fourth-grade students, and the school’s gardeners. Data collection includes observation, interviews, and documentation, followed by analysis stages of data reduction, presentation, and conclusion drawing, validated through peer examination. The findings illuminate several key points: (1) Teachers orchestrate the Pancasila Student Profile Strengthening Project (P5) at SDN Jombatan 6 Jombang, crafting tailored learning modules that align with the local environment. These modules are accompanied by practical actions derived from educational activities. (2) Strategies for implementing P5 activities in fourth-grade students are diverse, including material selection and engaging teaching methods to enhance knowledge acquisition. These efforts are supported by advocacy materials like banners or pamphlets. (3) The impact of P5 activities on students’ character at SDN Jombatan 6 Jombang is evident in their daily conduct, such as caring for plants, proper waste disposal, reducing plastic waste, bringing homemade lunches, participating in community service, and adhering to school regulations.